Exploring Phenomenon of Shadow Education in India - Sharma, Jinny; Mehra, Anjali (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
Shadow education or private tutoring or coaching classes is out of school help which provide educational help to the students in terms of subject understanding, revision, practice, doubt clearance etc. In India, earlier, its scope has been very limited to clear the board examination but in current times, shadow education has gone much beyond than this. Targeting entrance examinations, getting proficiency in English language, learning new skill has made non-formal sector of education more dynamic over the time. Rapid rise in the demand for shadow education has led in expansion of its reach. Economic reforms and change in the preferences of the stakeholders has added more to this. Against this background, the present study attempts to highlight the trend of coaching in the field of entrance examinations for the higher education institutions in the Country and to find the reasons behind its growth based on empirical review. The Study is based on secondary sources with thorough review of academic journals, industry reports, private or government publications etc. It has been found that Shadow Education market has become a big industry catering to the diversified demand of its stakeholders. There are several factors which have contributed in its growth such as system of entrance examinations for admission to higher educational institutes, loopholes in the working of formal school education and even rising expectations of parents.
Keywords: Coaching; Education; Coaching Companies; Entrance tests